EXPLORING THE USE OF LITERARY TEXTS FOR ENGLISH LANGUAGE LEARNING IN INDONESIAN SECONDARY EDUCATION - Rohmana, Wahyu Indah Mala (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This qualitative study explores the integration of literary texts for English language learning within Indonesian secondary education. The investigation sought to understand the diverse approaches and implementations of literature within the English learning curriculum in these educational settings. The data of this research was taken by interviewing 6 English teachers and 6 students in two secondary schools in Indonesia. The findings of the research revealed variations in the utilization of literary text across different schools. One school demonstrated a successful integration of literary texts into the English learning process, while another school showed shortcomings in incorporating literature effectively. Several factors contributing to the variance in successful implementation were identified, including insufficient knowledge among teachers about literature, limited incorporation of literary materials in English teaching, reduced student interest in English learning, disparities in the school curriculum, among other factors. This research highlights the need for a more comprehensive approach to the utilization of literature in English education within Indonesian secondary schools. It underscores the importance of addressing the identified factors to enhance the successful integration of literary texts, thereby improving the English learning experience for students across various educational institutions in Indonesia.